Analysis and Design of Data Warehouse for E-Library Using Snowflake Schema - Made Dwi Mulyawan; Ida Bagus Alit Swamardika; Komang Oka Saputra (International Journal of Engineering and Emerging Technology, 2020)
Information systems have become an important requirement in helping human work, one of which is e-library. Thissystem is used by librarians in carrying out daily business processes in the library, such as borrowing and returning books,managing book collections, and procuring the latest book collections so that the library has updated books. Over time, the datastored in the database will increase a lot, so when analyzing information that requires data with a certain period will take quite along time. So, in this case, the use of a data warehouse is needed to help the librarian in providing the information needed. Thisresearch will present a data warehouse design using snowflake schema by following the design stages in Fourth Steps DimensionalModeling, as one of the solutions in providing the required data warehouse design in the e-library.